Societal Conditions of the Policy of Nonalignment (Czech Journal of International Relations, 1967)
The policy of non-alignment arose in the period after the Second World War as a response to the beginning process of the formation of two antagonistic blocs. The very designation given to it by its protagonists defines it negatively, i.e. as a policy of non-participation in groupings, military pacts or political blocs. And if we use the term of any language, it seems to contain the negation or non-participation in these creations of the Cold War.This has led many analysts and politicians to assume non-engagement for a kind of peaceful neutrality, for a policy of tactics between the centers of individual blocs or for efforts to maintain the same distance between individual blocs. This opinion on the policy of non-alignment did not, understandably, originate from a misunderstanding or superficiality, but often from a deliberate underestimation of this policy or an effort to discredit it.This fact should be particularly emphasized, because it is one of the main methods the struggle against the policy of non-alignment during the Cold War was an attempt to obscure the goals and content of this policy with Russian obscurity or to distort them. In this regard, bloc-oriented propaganda has been making efforts for many years and has also achieved positive results in certain directions. One of them was the effort alone bearer of the policy of non-engagement to consider this policy as new, original and comprehensive world view. It was, in a certain sense, a reaction to contempt and criticism from the bloc.